Rancang Bangun Mesin Digesting Tandan Kosong Kelapa Sawit sebagai Bahan Baku Brown Paper - Hasibuan, Fauzatu Arabica Yatasya; Dina, Sari Farah; Tarigan, Krissandarta; Indriati, Lies (REACTOR: Journal of Research on Chemistry and Engineering, 2024)
Indonesia's pulp and paper production capacity was 5.5% of global production capacity in 2021. As an effort to support the development of the pulp and paper industry in Indonesia, pulp from empty oil palm fruit bunches (EFB) waste which are currently abundant is being tried to develope as raw material for brown paper. To simplify the process of developing pulp quality from EFB, the authors tried to design a rotary digester on a laboratory scale as a EFB digesting machine. The steps used in this research are assembling digester, making pulp, and finally analyzing the data. The digester machine was successfully designed to carry out the pulping process with operating conditions at a pressure of 7 bar, a temperature of 160°C, and a stirrer speed of 80 rpm with a maximum capacity of 1.3 L. The designed rotary digester is capable of producing pulp with an optimal yield level (43%) under reaction conditions, a temperature of 100°C and a NaOH concentration of 5%.